Immune Checkpoint Inhibitors in Melanoma Treatment: Advances and Obstacles - A. V. Sultanbaev (Креативная хирургия и онкология)
This paper presents a review of the state-of-the-art in skin melanoma treatment with a particular focus on immunotherapy and checkpoint inhibitors. Melanoma as a malignant neoplasm presents a serious threat given its high mortality rate, which emphasizes the need for further research and development of effective treatment strategies. Immune checkpoint inhibitors have shown a significant increase in the survival rate for skin melanoma patients. Nevertheless, the problem of drug resistance remains unresolved as a reaction to treatment differs from one patient to another even with high mutational burden. Obviously, immunotherapy may be accompanied by complications, which also emphasizes the need for an individualized approach to therapy. In order to predict treatment efficacy and understand possible resistance, mutation burden, T-cell receptor diversity, and specific antigens should be taken into account. All the above confirms the importance of a systematic approach to melanoma treatment including the use of modern drugs as well as a deep understanding of the patient’s immune status. Thus, this paper outlines the need for further research in the mechanisms of action of immunotherapeutic drugs as well as for the identification of biomarkers that may serve as predictors of response to therapy. This may lead to the development of more effective treatment strategies given the available advances in molecular biology and genetics. Addressing issues related to individualization of therapy based on immune status should become an important part of clinical practice.